Monitoring of Substructure Building of Suramadu Bridge Causeway Segment on Surabaya Side Based on Corrosion Level - Ari Setijorini; Anik Ratnaningsih; Krisnamurti Krisnamurti (U Karst, 2022)
The structure of the steel pile foundation for the Suramadu Bridge crossroad is located in a corrosive marine area. Air humidity, rainwater, mud, or friction with other objects that cause the protective layer to peel off. Corrosion monitoring is carried out to determine the corrosion rate as one of the steps to prevent corrosion. This study aims to evaluate and monitor the bridge's structure Suramadu Causeway. The evaluation carried out includes observing the damage caused by corrosion. So that it will be known the cause of corrosion and the handling of corrosion protection in the building under the bridge, this study used primary and secondary data collection methods and visual observation of damage from routine inspections carried out. The observations show that the condition of the piles is filled with marine life in the tidal area, while for areas that have never been submerged the condition is quite good. The value of the condition of the structural elements at level 3 - 5, which requires protection on steel pillars that have suffered a lot of damage—handling that needs to be done in the Atmospheric zone and Splash zone / Tidal zone is recommended Recoating, Wrapping, HDPE Jacketing, Epoxy Grouting. In the Submerged zone and the Embedded zone, it is recommended that the Cathodic Protection be replaced (120 kg for 600 mm). So from the results of the research that has been done, it can be used as a study for the maintenance of the Suramadu bridge in preventing corrosion.